Association between programmed cell death ligand 1 expression and thyroid cancer: A meta-analysis - Wan, Baoyu (Medicine (Baltimore), 2021)
BACKGROUND: Programmed cell death ligand 1 (PD-L1), which is highly expressed in a variety of malignant tumors, is closely related to clinicopathological features and prognosis. However, there are few studies on the potential effects of PD-L1 on thyroid carcinoma, the incidence of which has shown an upward trend worldwide. This study aimed to explore the association between PD-L1 expression and clinicopathological features and prognosis of thyroid cancer. METHODS: An elaborate retrieval was performed using Medline, PubMed, Cochrane Library, EMBASE, Web of Science, WanFang databases, and China National Knowledge Infrastructure to determine the association between PD-L1 expression and disease-free survival (DFS), overall survival (OS), and clinicopathological features in patients with thyroid cancer. Study selection, data extraction, risk assessment, and data synthesis were performed independently by 2 reviewers. In this meta-analysis, RevMan 5.3 and Stata 15.1 were used for bias risk assessment and data synthesis. RESULTS: After a detailed search, 2546 cases reported in 13 articles were included in this meta-analysis. The outcomes revealed that high expression of PD-L1 in patients with thyroid cancer was associated with poor DFS (hazard ratio [HR] = 3.37, 95% confidence interval [CI] 2.54–4.48, P < .00001) and OS (HR = 2.52, 95% CI: 1.20–5.32, P = .01). High PD-L1 expression was associated with tumor size ≥2 cm, tumor recurrence, extrathyroidal extension, concurrent thyroiditis, unifocal tumor, and absence of psammoma body (P < .05). Subgroup analysis showed that positive expression of PD-L1 was related to poor prognosis for DFS of non-medullary thyroid carcinoma, and the overexpression of PD-L1 in differentiated thyroid carcinoma (DTC) was related to tumor recurrence, concurrent thyroiditis, extrathyroidal extension, unifocal DTC, late stage DTC, and BRAF(V600E) mutation in DTC. CONCLUSION: PD-L1 is a significant predictor of prognosis and malignancy of thyroid cancer (especially DTC), and PD-L1 inhibitors may be a promising therapeutic option for refractory thyroid cancer in the future.